ANALISIS TINGKAT KEPUASAN PENGGUNA LULUSAN TERHADAP LULUSAN PENDIDIKAN VOKASI (STUDI KASUS LULUSAN POLITEKNIK LP3I MEDAN) - Zubaidah Hanum (Jurnal Ilmu Keuangan dan Perbankan, 2020)
This study aimed to know the level of satisfaction of companies that occupied Polytechnic LP3I Medan graduates. The sample of this study is purposive sampling. There were 22 relations companies Polytechnic LP3I Medan that occupy its graduates. The method in this study is Importance Performance Analysis (IPA). It is a method with identification of services quality level in a service industry which has 5 dimensions, such as Tangibles, Reliability, Responsiveness, Assurance, and Empathy. By analyzing the gap occurred because of the imbalance between priority level and graduates-user perception with services quality they got. Based on the study, it could be formulated that the company that occupy Polytechnic LP3I Medan graduates felt satisfied, even it hasn’t been as what they intend